Perencanaan Tebal Perkerasan Jalan Sergang – Jembatan Jengkong (No. 243) KM 8 Batu Putih Kabupaten Sumenep - Rakhman, Muhammad Baitur; Suwandi, Ahmad (Universitas Dr. Soetomo, 2019)
The white stone mine in Batu Putih Village is one of the natural resources located in Sumenep Regency, precisely on Sergang Street - Jengkong Bridge No. 243 Km 8. This road is the only access road to the white stone mining. The current condition of the road is damaged and interferes with the distribution process of white stones, so good thick pavement planning is needed. Planning of flexible pavement thickness and the cost of flexible pavement construction on Sergang - Jengkong Bridge No. 243 Km 8 Batu Putih, Sumenep Regency uses quantitative research. The data collection process uses two types of data, the first is primary data which includes LHR data and the second is secondary data which includes literature and literature studies. In this research the data analysis technique uses Microsoft Office Excel which is to calculate the budget plan and Autocad for drawing. For calculation procedures adjusted to SNI -1732-1989. The results of the Average Daily Traffic Survey (LHR) obtained the total number of vehicles passing through by 21164 smp. The road to be planned is 3 Km long and 4 m wide. Calculation of pavement thickness using the laston AC-WC is 2.50 cm thick and will be planned to be 4 cm thick. The planned budget (RAB) for the road planning is Rp. 2,613,171,000.00 (two billion six hundred thirteen million one hundred seventy-one thousand rupiah).